Marvin T. Herrick. Italian tragedy in the renaissance. The University of Illinois Press. Urbana. 1965. 315 págs., 23 x 14,5 cm. - Nallim, Carlos Orlando (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Literaturas Modernas, 1968)

(untitled)
Fil: Nallim, Carlos Orlando. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras